2016
DOI: 10.1042/cs20160183
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 deficiency protects against renal interstitial fibrosis in aldosterone/salt-treated mice

Abstract: Interleukin (IL)-18 is a member of the IL-1 family of cytokines and was described originally as an interferon γ-inducing factor. Aldosterone plays a central role in the regulation of sodium and potassium homoeostasis by binding to the mineralocorticoid receptor and contributes to kidney and cardiovascular damage. Aldosterone has been reported to induce IL-18, resulting in cardiac fibrosis with induced IL-18-mediated osteopontin (OPN). We therefore hypothesized that aldosterone-induced renal fibrosis via OPN ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…IL-18 promotes tissue injury such as kidney fibrosis and vascular inflammation in preclinical studies [14,15]. In this regard, serum IL-18 predicted 2-year cardiovascular mortality in patients at various stages of CKD with a past history of acute myocardial infarction [16].…”
Section: Cytokines As Uremic Toxinsmentioning
confidence: 99%
“…IL-18 promotes tissue injury such as kidney fibrosis and vascular inflammation in preclinical studies [14,15]. In this regard, serum IL-18 predicted 2-year cardiovascular mortality in patients at various stages of CKD with a past history of acute myocardial infarction [16].…”
Section: Cytokines As Uremic Toxinsmentioning
confidence: 99%
“…IL-18 is mainly produced by activated macrophages, which stimulate Th1 cells to secrete granulocyte-macrophage colony-stimulating factor, IFN- γ , and IL-2 and promote the proliferation of Th1 cells. IL-1 β and IL-18 can increase the expression of α -SMA protein in renal tubular epithelial cells, promote the transdifferentiation of renal tubular epithelial cells into myofibroblasts, and promote renal interstitial fibrosis [ 33 , 34 ]. Currently, the NLRP3 inflammasome is the most widely studied inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that IL-1β promotes the proliferation and myofibroblast transdifferentiation of HSCs with substantial increased levels of their fibrogenic markers (36)(37)(38). Activated caspase-1 could also cleave pro-IL-18 into its active form IL-18, and this cytokine has also been involved in fibrosis induction (38,39). In a murine model of non-alcoholic steatohepatitis, fibrosis was not reversed by IL-1Ra treatment, indicating that other regulators of NLRP3 inflammasome are involved in fibrogenesis promotion (33).…”
Section: Discussionmentioning
confidence: 99%